2003
DOI: 10.1038/sj.mp.4001443
|View full text |Cite
|
Sign up to set email alerts
|

The promoter −194 C polymorphism of the nicotinic alpha 7 receptor gene has a protective effect against the P50 sensory gating deficit

Abstract: As suggested by several studies, abnormal sensory gating measured by the P50 paradigm could be an endophenotype predisposing to schizophrenia. In a previous work, we have shown a significant association between the presence of at least one À2 bp deletion located within exon 6 of the CHRNA7-like gene and the P50 abnormality in the general population. A recent study involved polymorphisms located in the core promoter region of the CHRNA7 gene as risk factors for the P50 inhibitory deficit. Screening for promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 9 publications
2
31
1
Order By: Relevance
“…Furthermore, these SNPs are associated with both decreased promoter activity in vitro and failure to inhibit the P50 auditory-evoked response in humans. This finding, however, is not necessarily consistent with studies of other populations (Houy et al, 2004;Li et al, 2004).…”
contrasting
confidence: 56%
“…Furthermore, these SNPs are associated with both decreased promoter activity in vitro and failure to inhibit the P50 auditory-evoked response in humans. This finding, however, is not necessarily consistent with studies of other populations (Houy et al, 2004;Li et al, 2004).…”
contrasting
confidence: 56%
“…Linkage of this region to schizophrenia was further replicated in families from the NIMH Schizophrenia Genetics Initiative [40] and in other studies [41,42,43,44], but there have also been some negative studies in this region [45,46]. Multiple single nucleotide polymorphisms (SNP)have been identified in the 15q14 gene promoter region that are more frequently present in people with schizophrenia and their family members than normal controls [47,48]. Furthermore, the presence of a SNP in the 15q14 gene CHRNA7 5′ core promoter is significantly associated with P50 suppression deficits [47].…”
mentioning
confidence: 96%
“…Furthermore, the presence of a SNP in the 15q14 gene CHRNA7 5′ core promoter is significantly associated with P50 suppression deficits [47]. Association of CHRNA7 polymorphisms with P50 gating has been replicated, but the specific allelic associations differ, which suggests that responsible mutations have not yet been unambiguously identified [47,48]. In addition to the deficits in P50 evoked potentials and the functional promoter polymorphisms in the CHRNA7 region, people with schizophrenia also have abnormalities in expression and regulation of central nicotinic cholinergic receptors.…”
mentioning
confidence: 99%
“…Because of the problematic nature of ratios for statistical analysis (ie, a skewed distribution from 0 to values many times greater than the median), other genetic studies 38,55 of the P50 sensory gating paradigm have dichotomized the values into normal and abnormal. After completion of the initial analyses, a study by Anokhin et al 56 suggested that the difference between the test and conditioning amplitudes, an alternative measure often used with paired stimulus paradigms, 57 was more heritable than the ratio in a twin analysis.…”
Section: Heritabilitymentioning
confidence: 99%